ANALISIS YURIDIS ALAT BUKTI SURAT KETERANGAN DOKTER (STUDI PUTUSAN NOMOR 187/PID.SUS/2020/PN MLG) - Alwan Rasyid Naufal; Setiyono (Fakultas Hukum Universitas Trisakti, 2022)
Documentary evidence is one of the bases of proving a criminal case which is used before trial to help determine whether or not the defendant is guilty, and the judge who examines a criminal case must pay attention and examine the evidence provided before the trial. Article 54 of Law number 35 of 2009 concerning Narcotics stated that the victims of Narcotics Abuse and Addicts are required to undergo medical and social rehabilitation. But in practice, there are many narcotics abusers and addicts who are not given rehabilitation sentences but given punishment in the form of imprisonment. Therefore, the research’s problem are regarding the strength of doctor's certificate of evidence in narcotics crime case and the inaccuracy of legal considerations given by Panel of Judges regarding the doctor's certificate as evidence given before the trial. The research is a normative and descriptive analytical legal research, using secondary data obtain through library research, analyzed qualitatively and conclusions drawn using deductive understanding. The research conclusions are that the strength of documents as the evidence is independent and narcotics abusers should be given a punishment in the form of rehabilitation but in accordance with the existing and related regulations.